THE DYNAMICS FOR ANTI-HBV INFECTION TREATMENT WITH PEGINTERFERON ALFA-2A - VIRA AKMERIANA (NIM: 10108054) ; Pembimbing : Dr. Nuning Nuraini
This final project discussed model of dynamics for anti-HBV infection treatment with Peginterferon Alfa-2a for HBeAg-positive patients that had chronic hepatitis B. Construction of the model based on the basic model of virus (model prior to treatment), models after a given treatment for 56 days and 286 days with peginterferon alfa-2a and model after the 168 days of treatment was stopped. These models will consist the dynamics of host cells, virus-free and cytotoxic cells. Started with a review of hepatitis B, immune system and the model dynamics hepatitis B divide into three conditions as follow; before treatment, after treatment with Peginterferon Alfa-2a and after the treatment was stopped. These models will be analyzed using the stability of equilibrium points and numerical calculation to capture the dynamic of model for a certain period of time. These models capture the effects of the treatment of hepatitis B infection with Penginterferon Alfa-2a.